EFEKTIVITAS KONSELING BEHAVIORAL DENGAN TEKNIK MODELING MELALUI LESSON STUDY UNTUK MENINGKATKAN SELF NURTURANCE - Dharsana, I Ketut; Suarni, Ni Ketut; Adi Mahendra, I Gusti Ngurah (Mimbar Ilmu, 2019)
AbstrakTujuan penelitian ini adalah untuk mengetahui Efetivitas Konseling Behavioral Dengan Teknik modeling ?melalui lesson study untuk meningkatkan Self Nurturance ?siswa kelas X BDPM A SMK Negeri 1 Singaraja. Penelitian ini termasuk ?quasi exsperiment?. Desain eksperimen yang digunakan adalah Pretest Postest Control Group Design. Populasi penelitian ini adalah siswa siswi kelas X SMK Negeri 1 Singaraja yang berjumlah 71 siswa. Melalui teknik random sampling, 34 siswa ditempatkan dikelompok eksperimen dan 37 siswa ditempatkan pada kelompok kontrol. Metode pengumpulan data dalam penelitian ini menggunakan metode observasi, wawancara, buku harian dan kuesioner Self Nurturance. Kuesioner self nurturance telah teruji validitas dan realibilitasnya. Analisis data kuesioner menggunakan metode Alpha Cronbach. Penelitian in menggunakan uji Independent Samples t-test dengan bantuan JASP Version 0.7.5.5 menunjukkan nilai hasil uji hipotesis menggunakan Independent Samples t-test, mendapatkan t? = 9.347 dengan p < 0.05. Pengujian Effect Size (ES) menunjukkan tingkat keefektifan yang tinggi (ES= 2.221). Hasil tersebut membuktikan bahwa konseling behavioral dengan teknik modeling efektif untuk meningkatkan Self Nurturance siswa kelas X di SMK Negeri 1 Singaraja.?Kata-kata kunci : Konseling Behavioral, Lesson Study, Self Nurturance, Teknik Modeling?AbstractThis study aims to determine the difference of Fifth grade IPS learning outcomes of elementary school in Gugus II Tejakula Sub-district on even semester of 2017/2018 between group of students who are taught using Course Review Horay learning model with audio visual and group of students who are not taught using Course Review Horay learning model. This research is quasi experiment with non equivalent design post-test only control group design. The population of this study is all Fifth grade of elementary school students in Gugus II Tejakula sub-district academic year 2016/2017 in total of 162 students. The sample in this study is Fifth grade students of SD Negeri 5 Les in total 30 students and Fifth grade students of SD Negeri 1 Les counted 39 people, determined by random sampling technique. The result was obtained through multiple choice instrument test method which analyzed by using descriptive statistical and inferential statistical test (t-test). The result showed that there was a significant effect of IPS learning outcomes between groups of students who were taught using learning model of Course Reviews Horay helped by audio visual media and group of students who were not taught of using Course Review Horay model, with t-count = 2,384 bigger than t-tab = 1,980. This means that the difference application of learning model can affect the Fifth grade's IPS learning outcomes in Gugus II Tejakula sub-district even semester of academic year 2017/2018. Recommendation for the teachers in improving the Fifth grade's IPS learning outcomes in Sub-district II Tejakula is to use learning model of Course Review Horay assisted by audio visual media.?Keywords: Behavioral Counseling, Lesson Study, Self Nurturance, Modeling Techniqu